2020
DOI: 10.31983/jahmt.v2i3.5870
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Behavior of Outpatients in Controlling Hypertension in Tegal City

Abstract: Prevalensi penyakit hipertensi semakin meningkat. Data Riset Kesehatan Dasar (Riskesdas) menunjukkan peningkatan dari tahun 2013 sebesar 25,8% mejadi 34,1% pada tahun 2018. Pasien hipertensi, harus memiliki kemampuan dalam merawat dirinya secara mandiri, berupa meminum obat yang diresepkan, melakukan kontrol tekanan darah secara berkala, memodifikasi diet, menurunkan berat badan, serta meningkatkan aktivitas. Perilaku yang baik menjadi hal utama dalam keberhasilan perawatan mandiri  pasien hipertensi. Perilaku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
4
0
5
Order By: Relevance
“…In the quantitative and mixed-method studies, body weight management (29 studies 20 , 24 , 25 , 29 , 30 , 33 , 36 , 39–50 , 52 , 53 , 56–62 , 64 ) and physical exercise (22 studies 21 , 22 , 24 , 30–33 , 35 , 38 , 40–43 , 45 , 47 , 52 , 53 , 56 , 57 , 60 , 61 , 75 ) were the most reported, whereas in the qualitative studies, medication adherence and diet intake was the most reported self-care practice. In addition, a few studies described alternative self-care management methods such as stress-relieving methods (6 studies 35 , 40 , 60 , 66 , 68 , 75 ), sleep and rest (2 studies 68 , 74 ), and spiritual fulfilment was described in one study.…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…In the quantitative and mixed-method studies, body weight management (29 studies 20 , 24 , 25 , 29 , 30 , 33 , 36 , 39–50 , 52 , 53 , 56–62 , 64 ) and physical exercise (22 studies 21 , 22 , 24 , 30–33 , 35 , 38 , 40–43 , 45 , 47 , 52 , 53 , 56 , 57 , 60 , 61 , 75 ) were the most reported, whereas in the qualitative studies, medication adherence and diet intake was the most reported self-care practice. In addition, a few studies described alternative self-care management methods such as stress-relieving methods (6 studies 35 , 40 , 60 , 66 , 68 , 75 ), sleep and rest (2 studies 68 , 74 ), and spiritual fulfilment was described in one study.…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
“…In the quantitative and mixed-method studies, studies indicated that traditional self-care management, such as body weight management, physical exercise, dietary intake, and medication adherence were poorly practiced. Respectively, studies showed unaddressed risk factors for heart disease and stroke with a 50% incidence or more being reported for overweight/obese (8 studies 20 , 30 , 33 , 50 , 52 , 56 , 57 , 61 ), low level physical exercise (8 studies 21 , 24 , 31 , 32 , 45 , 56 , 57 , 61 ), poor/low-quality dietary intake (9 studies 21 , 23 , 30 , 34 , 40 , 56 , 57 , 60 , 75 ), and poor adherence to medication (4 studies 27 , 32 , 52 , 56 ).…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Perilaku CERDIK dan PATUH merupakan hal penting bagi pasien hipertensi (Prihandana et al, 2020). Penelitian sebelumnya menunjukan bahwa terdapat enam komponen penting yang dapat dilakukan dalam pengendalian tekanan darah seperti kepatuhan terhadap pengobatan, keaktifan dalam aktivitas fisik, dan pola makan rendah lemak, berat badan terjaga, kurangi minum minuman yang mengandung alkohol, serta hindari rokok (Zinat et al, 2016).…”
unclassified